Novel Proximal 14q Deletion: Clinical and Diffusion Tensor Imaging Tractography Findings in a Patient with Lissencephaly, Agenesis of the Corpus Callosum, and Septo-Optic Dysplasia - Bravo, E.K.; White, M.L.; Olney, A.H.; McAllister, J.L.; Zhang, Y.D. (American Journal of Neuroradiology, 2012)
SUMMARY: We report the unique CNS findings in a patient with a proximal chromosome 14q interstitial deletion. Conventional MR imaging allowed the clear delineation of agenesis of the corpus callosum, SOD, and diffuse lissencephaly. DTI tractography played a significant role in the evaluation of the proximal 14q deletion−associated abnormalities, delineating the extent of the dysmorphic connections of the Probst bundles and clarifying that apparent areas of heterotopias were the corticospinal tracts. FAfractional anisotropySODsepto-optic dysplasia